Covalent Organic Frameworks as a Biomacromolecule Immobilization Platform for Biomedical and Related Applications. Issue 10 (22nd July 2022) - Wang, Xinyue; Lewis, Damani A.; Wang, Gang; Meng, Tao; Zhou, Shengnan; Zhu, Yuheng; Hu, Danyou; Gao, Shan; Zhang, Guiyang
Abstract: With the development of biotherapeutic field, biomacromolecules with definite curative and small side effects have gradually become a hot spot in the research and development of new drugs. However, the use of biomacromolecules as drug candidates pose some technical difficulties related to their medicinal properties, mainly drug stability and in vivo transport and delivery. Currently, diverse nanodrug delivery systems have been used to deliver biomacromolecules because they can maintain stability, significantly increase bioavailability, and improve targeted distribution of biomacromolecules, thereby improving efficacy and reducing toxicity. In recent years, covalent organic frameworks (COFs) have attracted increasing interest as stable, efficient, and reusable biomacromolecule immobilization carriers. COFs exhibit good stability and biocompatibility with no biological toxicity, making them outstanding host materials for immobilizing biomacromolecules. However, the synthesis of COFs requires severe experimental conditions; the commonly used strategies for immobilizing biomacromolecules in metal–organic frameworks (MOFs), such as biomimetic mineralization, one‐pot synthesis, and coprecipitation, are likely not applicable to COFs. Herein, three strategies for immobilizing biomacromolecules in COFs and the multifunctional biomedical applications of the biomacromolecule@COF composite systems are reviewed. Next, the superior properties and cutting‐edge applications of MOFs are mentioned and then the advantages of COF–MOF hybrid materials are highlighted. Abstract : Covalent organic framework (COF)‐based vector systems are extensively developed as a new class of flexible and powerful platforms for delivering therapeutic biomacromolecules. Here, three strategies for immobilizing biomacromolecules in COFs and the multifunctional biomedical applications of the biomacromolecules@COFs composite systems are reviewed. Then, their particularity in synthesis and their advantages in applications compared to metal–organic framework systems are highlighted.